EPITHELIOTROPIC CUTANEOUS LYMPHOMA IN A SHIH-TZU DOG - Emanuelle Drago; Flávio Gabriel Gaede Scardua; André Luiz Leite de Sousa; Haide Valeska Scheid; Fernanda Cristina de Abreu Quintela Castro; Clairton Marcolongo Pereira (UNESC em Revista, 2025)
Canine cutaneous epitheliotropic lymphoma (CEL) is a rare malignant neoplasm characterized by the infiltration of neoplastic T lymphocytes in the epidermis and adnexal structures. It predominantly affects older dogs and presents with variable clinical signs, often delaying diagnosis. This report describes the clinicopathological features of CEL in a Shih Tzu. The patient presented with multiple erythematous and crusty skin lesions. Histopathological analysis revealed diffuse infiltration of neoplastic T lymphocytes, Pautrier microabscesses, adnexal involvement, and a high mitotic index. Although immunohistochemistry is recommended for definitive classification, it was not performed in this case because of financial limitations. The clinicopathological findings were consistent with the mycosis fungoides form of CEL. The clinical presentation resembles that of chronic inflammatory dermatoses, making early diagnosis challenging. The scarcity of reported cases in Shih Tzus underscores the importance of this case in broadening the breed-specific knowledge. This case highlights the need for clinical suspicion and histopathological confirmation in dogs with chronic dermatoses, especially in underreported breeds, such as Shih Tzus. Keywords: T-cell lymphoma, Skin, Histopathology, Dogs, Mycosis Fungoides, Shih Tzu